Legal Protection For Digital Bank Customers Without Branch Offices In Resolution Of Banking Complaints And Disputes In Indonesia - Ade Uli Kurniati Siregar (PT. Hafasy Dwi Nawasena, 2026)
The development of digital technology has given rise to a banking service model that allows customers to access various banking services without having to visit a branch office. Digital banks offer the convenience of opening accounts, transferring funds, making payments, depositing funds, and other services through applications or electronic means. However, the characteristics of digital banks, which do not rely on conventional branch offices, pose unique challenges in terms of legal protection for customers, particularly when customers experience problems and require in-person service or complaints. These issues become more complex when unauthorized transactions, account blocking, loss of funds, system disruptions, transaction failures, misuse of personal data, or other issues requiring immediate resolution occur. This study aims to analyze the legal protection for customers of digital banks without branch offices and analyze the complaint and dispute resolution mechanisms that customers can use when experiencing problems. This study uses a normative juridical method with a statutory and conceptual approach. The results show that the absence of physical branch offices does not eliminate the obligation of digital banks to provide customers with access to complaints and dispute resolution. Digital banks are required to provide effective, accessible, transparent, and accountable complaint channels. If complaints to the bank are not resolved, customers can use dispute resolution mechanisms in the financial services sector in accordance with applicable regulations. Therefore, legal protection for digital bank customers must ensure that limited physical interaction does not become an obstacle for customers to obtain justice and resolution when experiencing losses.